Nutritional Assessment of Cakes Developed by Incorporating Partially Defatted Peanut Flour in The Process - Geraldo, Nasser Farid (Proceeding International Conference on Science and Engineering, 2021)
Abstract. In Benin the residue of peanut oil extraction is very useful. This partially defatted peanut flour produced by mechanical pressing have many potentials uses in foods. The defatted peanut flour has a high protein solubility and is light colored, practically tasteless, and odor free. The defatted peanut flour has been evaluated as: an additive to increase the protein content of foods such as bread and other baked foods. The aim of this study was to assess the effect of substitute partially defatted peanut flour (PDPF) flour in place of wheat flour (WF) on the nutritional and sensory properties of plain cake and eggless cake. Four formulations without control of each types of cake were prepared by incorporating partially defatted peanut flour at different levels (10-20%). The partially defatted peanut flour was prepared from their dried and roasted peanut. The developed products were evaluated for sensory attributes by using nine point hedonic rating scale and nutritional composition of the products was assessed by using standard methods. At 10 percent, plain cake and eggless cake were more acceptable with overall acceptability being 7.88, 7.92. The developed products were found to be highly nutritious in terms of protein, iron and calcium. The developed products with incorporation were found to be comparable to their respective control samples in terms of proximate analysis except for protein, fibre and calcium content which significantly increased in all the products. From the various fortified products, eggless cake showed a maximum protein content i.e. 10.59 percent. Fat for all products significantly increased as compared to their respective control samples. Maximum fibre content and ash content was found in eggless i.e. 0.58 g/100g and 1.55mg/100g respectively on dry weight basis. The highest energy content was found in plain cake as 519.82 Kcal. The maximum calcium content was found in eggless cake as 65.63 mg/100g. Value added baked products using peanut flour can be supplemented to the community to improve the nutritional status. Keeping in view the nutritional value of peanut flour, it can be highly recommended to the bakery industry to incorporate peanut flour in their products and thus improve its nutritive value. Keywords: Cake, Nutritional composition, Partially defatted peanut flour.